Conjunctival Retention Cysts: Outcomes of Aspiration and Sclerotherapy With Sodium Tetradecyl Sulfate. Issue 2 (March 2019) - Dave, Tarjani; Taneja, Shikha; Tiple, Sweety; Basu, Sayan; Naik, Milind N.
Abstract : Purpose: To assess the outcome of aspiration and sclerotherapy with sodium tetradecyl sulfate in the management of conjunctival inclusion cysts. Methods: Retrospective interventional case series of 6 patients with clinical diagnosis of conjunctival inclusion cysts treated with cyst aspiration and foam sclerotherapy with 3% sodium tetradecyl sulfate. The volume of the sclerosant was 20% of the aspirated cyst volume. Results: Four patients had an inclusion cyst in anophthalmic sockets and 2 patients in sighted eyes. Average time lag between primary surgery and cyst formation was 14.6 months (range 2–30 months). Average amount of fluid aspirated from cyst was 3.07 ml (range 1–9 ml). Average volume of sclerosant injected was (20% of the aspirated volume) 0.55 ml (range 0.2–1.1 ml). All 6 patients showed complete resolution of cyst at a mean follow-up period of 15.6 months (range 9–24 months). All but one showed complete resolution of cyst with single injection sclerosant. Only 1 patient required a second sclerosant injection. There was no ocular surface or implant-related complications in this cohort. Conclusions: Cyst aspiration and sodium tetradecyl sulfate foam sclerotherapy is a minimally invasive procedure for the management of conjunctival inclusion cysts in anophthalmic sockets and sighted eyes. The injection of sodium tetradecyl sulfate in a dose of 20% of the aspirate is effective in the management of conjunctival inclusion cysts over a follow-up period of 13 months. The procedure is safe, with insignificant inflammation and without ocular surface or implant complications. Abstract : Six patients with conjunctival inclusion cysts, 4 in anophthalmic sockets and 2 in sighted eyes, were treated with cyst aspiration and sclerotherapy with sodium tetradecyl sulfate. Over an average follow-up period of 13 months, none of the cysts recurred and there were no additional eye or procedural complications noted.